A scientific transition to support the 21st century dietary transition. (January 2023) - Tufford, Adèle Rae; Brennan, Lorainne; van Trijp, Hans; D'Auria, Sabato; Feskens, Edith; Finglas, Paul; Kok, Frans; Kolesárová, Adriana; Poppe, Krijn; Zimmermann, Karin; van 't Veer, Pieter
Structured Abstract: Background: Eating habits must change substantially in order to address the urgent societal challenges of personal, public and planetary health. Research surrounding various facets of the dietary transition remains siloed, hindering breakthroughs. Scope and approach: We argue the scientific case for transdisciplinary research centered around the transition to healthy, sustainable, and acceptable diets. This transition requires tackling the broad societal challenges of engaging consumers in the diet transition, improving nutritional health and achieving environmental sustainability of foods and food systems. Key findings: The crucial synergies and trade-offs from addressing single challenges in isolation are discussed, as well as obstacles when considering the collaboration between the multiple scientific disciplines concerned with the dietary transition. Currently, interactions between these challenges remain understudied and/or ambiguous, in part due to a lack of interoperable data and standards. Intersectional research entry points acting at the intersection of the three challenges are explored: food taste and texture reformulation, food pricing strategies and food literacy. The implementation of such cross-cutting interventions urgently requires both the generation of new data and exploitation of the breadth of existing data. Researchers must therefore be facilitated to find, access and use interoperable data to model and measure food intake and all its determinants. Conclusions: The dietary transition requires underpinning by a research infrastructure that supports access to transdisciplinary data, facilities and research tools, alongside training and capacity building. Filling these unmet data, tools and training needs is the first step towards delivering breakthrough innovations to foods and food environments, mobilizing consumers to engage in the dietary transition. Highlights: Current research on healthy and sustainable diets ignores critical synergies and trade-offs between research domains. The challenge for research on the diet transition is to address inter- and trans -disciplinary research entry points. Fragmented data, methods and training require a transdisciplinary research infrastructure addressing the diet transition. A transdisciplinary research infrastructure needs underpinning by permissive policy environments and research agendas.